Development of the Shaking Table and Array System Technology in China - Chun-hua Gao; Xiao-bo Yuan (Advances in Civil Engineering)
Shaking table is important experimental equipment to carry out antiseismic research. Research, conclusion, comparison, and analysis concerning the developmental history, constructional situation, performance index, control algorithm, and experimental technique of the internal shaking table were reviewed and compared. Such functional parameters as internal shaking table’s table-board size, bearing capacity, working frequency, and maximum acceleration were given. Shaking table’s constructional status quo and developmental trend were concluded. The advantages and disadvantages of different control algorithms were contrastively analyzed. Typical shaking table test, array system tests, and experimental simulation materials were induced and contrasted. Internal existing shaking table and array system test’s structural type, reduced scale, and model-material selection were provided. Analysis and exposition about the developmental tendency of shaking table’s enlargement, multiple shaking tables array, full digitalization, and network control were made. The developmental direction, comparison of technical features, and relevant research status quo of shaking table with high-performance were offered. The result can be reference for domestic or overseas shaking table’s design and type selection, control technique, and research on experimental technique.